The impact of anxiety on the cognitive function of informal Parkinson’s disease caregiver: Evidence from task-based and resting-state fNIRS - Wang, Hai-Yang; Ren, Lu; Li, Tao; Pu, Lanlan; Huang, Xiaofeng; Wang, Song; Song, Chunli; Liang, Zhanhua (Frontiers in Psychiatry, 2022)
Informal Parkinson’s disease (PD) caregivers are considered to experience high levels of caregiver burden, negatively affecting the health of caregiver. However, few studies have explored the relationship between anxiety in caregiver burden and cognitive function in informal PD caregiver. Even no study has investigated neural mechanisms underlying this connection. This study aimed to conduct comprehensive cognitive and clinical assessment and evaluate brain activity from task-based and resting-state using functional near-infrared spectroscopy (fNIRS). Ten informal PD caregivers and 15 matched, healthy, non-caregivers were recruited. Comprehensive cognitive and clinical assessments were conducted to evaluate five cognitive domains and mental state. Neural activity induced by verbal fluency task (VFT) and brain connectivity during resting-state were monitored, and their correlations with neuropsychological and clinical test was explored. Our results showed compared to non-caregiver, informal PD caregiver exhibited no differences in most cognitive domains of function, but performed better in attentional function, along with higher levels of anxiety. Decreased activation over prefrontal regions during VFT and hypo-connectivity within frontoparietal network (FPN) and between default mode network (DMN) and FPN in resting state was confirmed in this study as a result of negative effects of anxiety on the brain. Furthermore, Spearman correlation found neural activity in FPN during task-based and resting-state were negatively correlated with severity of anxiety. These findings indicate that despite normal or even better cognitive function, informal PD caregivers actually have impaired brain function, and this deficit in neural activity was related to anxiety.